Deleterious Effects of SARS-CoV-2 Infection on Human Pancreatic Cells - Shaharuddin, Syairah Hanan; Wang, Victoria; Santos, Roberta S.; Gross, Andrew; Wang, Yizhou; Jawanda, Harneet; Zhang, Yi; Hasan, Wohaib; Garcia, Gustavo; Arumugaswami, Vaithilingaraja; Sareen, Dhruv (Frontiers in Cellular and Infection Microbiology, 2021)
COVID-19 pandemic has infected more than 154 million people worldwide and caused more than 3.2 million deaths. It is transmitted by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and affects the respiratory tract as well as extra-pulmonary systems, including the pancreas, that express the virus entry receptor, Angiotensin-Converting Enzyme 2 (ACE2) receptor. Importantly, the endocrine and exocrine pancreas, the latter composed of ductal and acinar cells, express high levels of ACE2, which correlates to impaired functionality characterized as acute pancreatitis observed in some cases presenting with COVID-19. Since acute pancreatitis is already one of the most frequent gastrointestinal causes of hospitalization in the U.S. and the majority of studies investigating the effects of SARS-CoV-2 on the pancreas are clinical and observational, we utilized human iPSC technology to investigate the potential deleterious effects of SARS-CoV-2 infection on iPSC-derived pancreatic cultures containing endocrine and exocrine cells. Interestingly, iPSC-derived pancreatic cultures allow SARS-CoV-2 entry and establish infection, thus perturbing their normal molecular and cellular phenotypes. The infection increased a key cytokine, CXCL12, known to be involved in inflammatory responses in the pancreas. Transcriptome analysis of infected pancreatic cultures confirmed that SARS-CoV-2 hijacks the ribosomal machinery in these cells. Notably, the SARS-CoV-2 infectivity of the pancreas was confirmed in post-mortem tissues from COVID-19 patients, which showed co-localization of SARS-CoV-2 in pancreatic endocrine and exocrine cells and increased the expression of some pancreatic ductal stress response genes. Thus, we demonstrate that SARS-CoV-2 can directly infect human iPSC-derived pancreatic cells with strong supporting evidence of presence of the virus in post-mortem pancreatic tissue of confirmed COVID-19 human cases. This novel model of iPSC-derived pancreatic cultures will open new avenues for the comprehension of the SARS-CoV-2 infection and potentially establish a platform for endocrine and exocrine pancreas-specific antiviral drug screening.